answersLogoWhite

0


Best Answer

plus 4, minus 3

User Avatar

Wiki User

11y ago
This answer is:
User Avatar

Add your answer:

Earn +20 pts
Q: What the pattern for 1 5 2 6 3 7?
Write your answer...
Submit
Still have questions?
magnify glass
imp
Related questions

What are the increments of the pattern 1 2 5 14?

this series increments in powers of 3 like 1+3^0=2 2+3^1=5 5+3^2=14 14+3^3=41 and so on....


What is the pattern 1-1-2-3-5-8-13-21?

You add the 2 numbers before e.g. 2+3=5


What is the number pattern for 1 2 3 5 7?

11


What is the pattern of the Fibonacci numbers?

0, 1, 1 (0+1), 2 (1+1), 3 (2+1), 5 (2+3), 8 (3+5), 13(5+8), 21 (13+8), 34 (21+13),....and so on.


What is a math sequence?

it is basically a pattern e.g. 1 2 3 4 5 6 7 8 9 10 11 1 2 1 3 1 4 1 5 1 6 3 1 4 1 5 9 2 6 5 3 5 8 9 7 9


What is the pattern rule for this pattern 1-3-2-6-5-15-14-42-41?

Start at 1. Multiply by 3. Subtract 1. Multiply by 3. Subtract 1. Repeat this pattern.


What is the pattern for 1 1 2 3 5 8 and more?

1+1=2 1+2=3 2+3=5 3+5=8 5+8=13 8+13=21 13+21=34 and so on. In each case, n=n becomes the next additional calculation.


What comes next in the pattern 5 ten 3 8 1?

2


What is the pattern rule for this pattern 1 3 2 6 5 15 14 42 41?

The answer is (no.) x3 = (no. 2) - 1 = (no. 3) x3= (no.4) x4 and so on... 1 x 3 = 3 - 1 = 2 x 3 = 6 - 1 = 5 x 3 = 15 - 1 = 14 x 3 = 42 - 1 = 41. :D Hope i helped


What is the pattern in 5 -1 2 -4 -1?

minus 6, plus 3, minus 6, plus 3...


What is a Fibonacci number pattern?

You start with two integers, usually 0 and 1 or 1 and 1 and get the next number in the pattern by adding the two previous numbers. For example starting with 1 and 1 , 1 + 1 = 2 ,so the sequence is now 1 1 2 1+ 2 = 3 , so the sequence is 1 1 2 3 2+3 = 5 . " " " " 1 1 2 3 5 The formula is an = an-1 + an-2. where a0 and a1 are given and n > 1.


How do you rationalize the denominator in this expression 5 divided by square root of 3 minus 1?

5/(√3 - 1)= 5(√3 + 1)/(√3 - 1)(√3 + 1)= (5√3 + 5)/[(√3)2 - 12)= (5√3 + 5)/(3 - 1)= 5√3 + 5)/2= 5√3/2 + 1/2